Structure, configuration, and sizing of Ni nanoparticles generated by ultrafast laser ablation in different media - Muñetón Arboleda, David (2015)
In recent years, nickel nanoparticles (NPs) have increased scientific interest because of their extensive prospects in catalysts, information storage, large-scale batteries and biomedicine. Several works on Ni NPs generation by laser ablation have appeared in the literature in the last years, using different pulsed laser regimes and different media have been published recently. In this work we analyze the characteristics of species, structure (bare core or core-shell), configuration and size distribution of NPs generated by fs pulse laser ablation over a Ni solid target in n-heptane and water. We explore the presence of NiO-Ni core-shell and hollow Ni (or air-Ni) NPs in the colloids obtained. These were experimentally characterized using AFM and TEM microscopy, as well as Optical Extinction Spectroscopy (OES). Extinction spectra were modeled using Mie theory through an appropriate modification of the complex experimental dielectric function, taking into account a size-dependent corrective term for each free and bound electron contribution. Experimental UVvisible- NIR spectra were reproduced considering a size distribution of bare core, hollow and core-shell structures NPs. In both media, Ni NPs shape and size distribution agrees with that derived from TEM and AFM analysis.